A Path-based approach to Managing Information Systems in Operations - Upton, D; McAfee, A (2000)
Two archetypal approaches to performance improvement in operations are to undertake periodic ''strategic leaps'' or to take frequent small actions in a quest for ''continuous improvement''. Much research on the implementation of advanced manufacturing technologies (AMTs) indicates that even though their introduction appears to be a strategic leap, principles of continuous improvement can be important in determining success. Three such principles are: modularity, accessibility, and inclusiveness. These principles are applied to non-shop floor information technology, an important category of AMT. The monolithic information technologies that have historically been dominant are characterised both by low levels of modularity, accessibility and inclusiveness, and by an installation-based approach to implementation. Recent innovations, however, permit a substantively different, path-based approach. The migration from installation- to path-based approaches is illustrated with the example of enterprise resource planning (ERP) systems. The modularity and accessibility of ERP systems appear to be improving, while inclusiveness lags.